Suspected predatory bites on a snorkeler by an oceanic whitetip shark Carcharhinus longimanus off Moorea island (French Polynesia). Issue 6 (21st August 2021) - Clua, Eric E. G.; Demarchi, Simon; Meyer, Carl G.
Abstract: Understanding why sharks bite humans is essential for developing strategies to prevent these incidents. Here, we use bite wound characteristics and eye witness descriptions of shark behavior to determine the likely motivation for several bites perpetrated by an oceanic whitetip (OWT) shark Carcharhinus longimanus on an adult female snorkeler off Moorea island (French Polynesia) in October 2019. The victim was snorkeling with others in pelagic waters as part of an organized whale‐watching tour when the shark—without any warning behavior—bit her at least three times resulting in severe injuries with substantial loss of soft tissue from the chest and both forearms. The victim survived these injuries thanks to rapid and effective first aid provided by her companions. The sudden, unprovoked and repeated bites with substantial tissue removal are consistent with predatory behavior although the dominance hypothesis cannot be fully ruled out. This would be the first case of a predatory shark bite ever documented in French Polynesia in over 70 years of data collection. Given the routine association of OWT sharks with cetaceans, in‐water whale watching activities should adopt appropriate risk management strategies in regions hosting this species of shark.